Safety and effectiveness of switching to Abacavir/Lamivudine plus rilpivirine for maintenance therapy in virologically suppressed HIV-1 individuals in Singapore (SEALS) - Z. C. Lim (BMC, 2021)
Abstract Background The efficacy and tolerability of an antiretroviral regimen are important considerations for selection of HIV-1 infection maintenance therapy. Abacavir/lamivudine plus rilpivirine (ABC/3TC + RPV) has been shown in international studies to be effective and well-tolerated in virologically suppressed individuals. This study evaluated the effectiveness and safety of switching to ABC/3TC + RPV as maintenance therapy in virologically suppressed HIV-1 infected individuals in Singapore. Methods In this retrospective, single-centre study, we included individuals who were prescribed ABC/3TC + RPV, had HIV-1 viral load (VL) < 50 copies/ml immediately pre-switch, and had no documented history of resistance mutations or virologic failure to any of the components. The follow-up period was 48 ± 12 weeks. The primary outcome was the proportion of individuals who maintained virologic suppression of HIV-1 VL < 50 copies/ml at the end of follow-up period based on on-treatment analysis. The secondary outcomes were the resistance profiles associated with virologic failure, changes in immunologic and metabolic parameters, and the safety profile of ABC/3TC + RPV. Results A total of 222 individuals were included in the study. The primary outcome was achieved in 197 individuals [88.8%, 95% confidence interval: 83.7–92.4%]. There were 21 individuals (9.5%) who discontinued treatment for non-virologic reasons. The remaining 4 individuals experienced virologic failure, of whom, 3 of these individuals had developed emergent antiretroviral resistance and had HIV-1 VL > 500 copies/ml at the end of the 48 ± 12 weeks follow-up period. The remaining individual experienced sustained low level viremia and subsequently achieved viral suppression without undergoing resistance testing. A total of 49 adverse events were observed in 31 out of 222 individuals (14.0%), which led to 13 individuals discontinuing therapy. Neuropsychiatric adverse events were most commonly observed (53.1%). A statistically significant increase in CD4 was observed (p < 0.01), with a median absolute change of 31 cells/uL (interquartile range: − 31.50 to 140.75). No significant changes in lipid profiles were detected. Conclusion ABC/3TC + RPV is a safe and effective switch option for maintenance therapy in virologically suppressed HIV-1 individuals with in Singapore.